AN ANALYSIS OF STUDENTS' READING STRATEGIES BASED ON GENDER AT SMAN 3 BATUSANGKAR - Yendoris, Febri; Ardhi, Havid (University of Kuningan, 2025)
The ability to read well is very important for students to understand and process information effectively, especially in the context of learning. Reading ability is closely related to the strategies used by students, where the better the strategy used, the better the information obtained. This study aims to analyze the differences in reading strategies based on gender in class XI students at SMAN 3 Batusangkar. Using a comparative descriptive research design, three reading strategy variables Global (GLOB), Support (SUP), and Problem Solving (PROB) were analyzed. The results showed that male and female students used similar reading strategies, with average scores ranging from 54.0 to 63.5. Male students tended to excel more in the SUP and GLOB strategies, while female students excelled more in the PROB strategy, although the difference was relatively small. The study concluded that although there were differences in strategy use based on gender, the differences were not statistically significant. This finding indicates that gender is not the main determining factor in students' choice of reading strategies.